ESTUDO DA VIABILIDADE DA PRODUÇÃO DE BIODIESEL, A PARTIR DA SOJA E GIRASSOL, NA REGIÃO FRONTEIRA NOROESTE/RS - PETRY, DÉBORA; SAUGO, DIEGO; BRAUN, FELIPE; KUNZ, JULIANE; ZINGLER, KARINE; CÔAS, MAURÍCIO; BRUM, ARGEMIRO L.; SOUZA, JOSÉ D. D. S. (Salão do Conhecimento, 2013)
Resumo